Desain Media Pembelajaran E-Modul dengan Pendekatan Culturally Responsive Teaching (CRT) Materi Kesebangunan dan Kekongruenan - Mecca Evi Novianti; Dwi Sulistyaningsih; Venissa Dian Mawarsari (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Balikpapan, 2026)
The advancement of electronic systems necessitates modernization in mathematics learning to render it increasingly collaborative and aligned with scholars’ requirements. In execution, learning regarding the material of similarity and congruence at the junior high school tier continues encountering numerous obstacles, especially concerning pupils’ restricted theoretical grasp and the inefficient utilization of electronic learning media. This study aims to develop an e-module based on the Culturally Responsive Teaching (CRT) approach on similarity and congruence material that meets validity criteria as a learning resource. This investigation utilized a Research and Development (R&D) strategy employing the 4D framework, which was performed until the define, design, and develop phases. Evidence was gathered through verification forms finalized by media specialists and material authorities. The findings demonstrated that the e-module achieved a mean rating of 3.88 from media experts and 3.69 from material experts using a 1-4 scale, with an overall mean score of 3.78, which was categorized as highly valid. These outcomes signify that the produced e-module satisfies the viability benchmarks for application in learning. The produced e-module is anticipated to assist pupils in comprehending principles via dynamic learning exercises unified with the societal background of Nyadran. Subsequent exploration is advocated to scrutinize the usability and efficacy of the e-module within class execution.